2004
DOI: 10.1300/j070v13n03_13
|View full text |Cite
|
Sign up to set email alerts
|

Recidivism and Resilience in Juvenile Sexual Offenders: An Analysis of the Literature

Abstract: The majority of research that exists studying juvenile sex offenders (JSOs) is dominated by the predilection that identifying risk factors associated with recidivism will benefit both the JSOs and treatment providers. Further, the majority of existing treatments are guided by research that has identified what makes JSOs more likely to reoffend. Absent from the majority of the literature is an examination of the strengths and positive characteristics demonstrated by JSOs that may prove useful in both reducing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Recently, there has been an increased interest in studying protective factors that appear to serve individuals to avoid offending behaviors and to assist in a successful return to community settings; this research has been conducted among vulnerable populations such as forensic psychiatric patients and offenders (Nicholls et al, ; de Vogel et al, ; Webster et al, , ; Wilson, Desmarais, Nicholls, & Brink, ). Historically, however, research on successful community reintegration and desistance from offending behavior has centered around juvenile offenders in terms of the trajectory of desistance in the transition from adolescence into adulthood (Aspy et al, ; Carr & Vandiver, ; Efta‐Breitbach & Freeman, ; Fergus & Zimmerman, ; Hjemdal, Aune, Reinfjell, Stiles, & Friborg, ). Consequently, there is a stronger understanding of desistance of offending behavior and successful community reintegration within youth populations than has been developed in the adult forensic literature.…”
mentioning
confidence: 99%
“…Recently, there has been an increased interest in studying protective factors that appear to serve individuals to avoid offending behaviors and to assist in a successful return to community settings; this research has been conducted among vulnerable populations such as forensic psychiatric patients and offenders (Nicholls et al, ; de Vogel et al, ; Webster et al, , ; Wilson, Desmarais, Nicholls, & Brink, ). Historically, however, research on successful community reintegration and desistance from offending behavior has centered around juvenile offenders in terms of the trajectory of desistance in the transition from adolescence into adulthood (Aspy et al, ; Carr & Vandiver, ; Efta‐Breitbach & Freeman, ; Fergus & Zimmerman, ; Hjemdal, Aune, Reinfjell, Stiles, & Friborg, ). Consequently, there is a stronger understanding of desistance of offending behavior and successful community reintegration within youth populations than has been developed in the adult forensic literature.…”
mentioning
confidence: 99%
“…Future research efforts should also be dedicated to resiliency. There is a dearth of research on protective factors -those factors and processes that buffer youths from engaging in high-risk behaviours, sex offending in particular (Efta-Breitbach & Freeman, 2004). However, there is a general literature base on resilience broadly, from which inferences can be drawn to strengthen programming (Efta-Breitbach & Freeman, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Research with youth offenders has suggested that resilience is a factor that may help offenders avoid or desist from offending (Efta-Breitbach & Freeman, 2004) and as noted above, resilience is included as a protective factor in at least one risk assessment instrument (the SAVRY; Borum et al, 2000). Despite this, resilience has received scant empirical attention within the offending literature (Fougere & Daffern, 2011).…”
Section: Resilience and Offendersmentioning
confidence: 99%
“…One construct that has received attention as a potential protective factor against reoffending is resilience (Borum et al, 2000;Efta-Breitbach & Freeman, 2004), and indeed some risk assessment measures specifically include items on resilience (i.e. the Structured Assessment of Violence Risk in Youth [SAVRY]; Borum et al, 2000).…”
mentioning
confidence: 99%